2002
DOI: 10.1111/j.1748-0361.2002.tb00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Incidence and Mortality in Texas 1990–1992: A Comparison of Rural Classifications

Abstract: Although cancer incidence and mortality rates are known to be higher in urban populations, more unstaged tumors and later staged cancer are diagnosed in rural populations. Most investigators have used a dichotomous definition of urban and rural in studying these populations, and they have not considered whether a more detailed categorization of rural areas could influence their findings. The objective of this study was to evaluate colorectal cancer incidence and mortality rates in Texas from 1990 to 1992 by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
(15 reference statements)
2
25
0
Order By: Relevance
“…46 Hawley used both RUCCs and UICs to describe the variation in colon cancer incidence and mortality rates in Texas and concluded that finer delineations on the rural end of the scales revealed heterogeneity in rates with respect to African-Americans. 47 Similarly, we found much lower rates of mammography-detected breast cancer in North Carolina (NC) in the most rural areas using the UIC taxonomy; these differences would have been attenuated had we used a dichotomous measure. 48 Researchers have also grouped the scales.…”
Section: Us Census Urban and Ruralmentioning
confidence: 83%
“…46 Hawley used both RUCCs and UICs to describe the variation in colon cancer incidence and mortality rates in Texas and concluded that finer delineations on the rural end of the scales revealed heterogeneity in rates with respect to African-Americans. 47 Similarly, we found much lower rates of mammography-detected breast cancer in North Carolina (NC) in the most rural areas using the UIC taxonomy; these differences would have been attenuated had we used a dichotomous measure. 48 Researchers have also grouped the scales.…”
Section: Us Census Urban and Ruralmentioning
confidence: 83%
“…To our knowledge, this is the first population‐based study in Nebraska using data from the state's cancer registry that used the 3‐level OMB classification scheme (rural [non‐core] nonmetropolitan, micropolitan nonmetropolitan, and metropolitan) and other determinants of early‐stage CRC diagnosis. Unlike previous studies that used dichotomous schemes, 3,4,6,7,22 we used the recent 2003 OMB classification, 23–27 and controlled for other confounders of early‐stage CRC diagnosis, such as socioeconomic status (income and education), health insurance, anatomic site, and provider‐to‐population ratio, in 1 multivariate model. The reported findings of rural/micropolitan differences but no rural/metropolitan differences for early‐stage ( in situ /local) were upheld for “ in situ ” CRC diagnosis (data not shown), which supports the robustness of our results.…”
Section: Discussionmentioning
confidence: 99%
“…Dichotomous definition of rural‐urban communities in previous studies 3,4,6,7,22 may mask important differences in CRC incidence, 22 and misclassify a proportion of the rural population that may be affected by nonmetropolitan diversity 23 . The federal government frequently uses the county‐based OMB metropolitan and nonmetropolitan classifications as policy tools in determining eligibility and reimbursement for many federal programs 24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the efforts, discrimination based on socioeconomic status and location continues to play an important role in colorectal cancer outcomes. According to a recent review, one half of patients in rural areas are not up to date on colorectal cancer screening [10,11]. Moreover, marked disparities persist, with lower rates of colorectal cancer screening among racial and ethnic minorities, individuals with lower household income, lower levels of education, the uninsured, and individuals who were not born in the United States [12-15].…”
Section: Introductionmentioning
confidence: 99%